2010
DOI: 10.1108/17554191011084157
|View full text |Cite
|
Sign up to set email alerts
|

Development of multidimensional scale for healthcare service quality (HCSQ) in Indian context

Abstract: Purpose -The purpose of this paper is to develop and empirically validate a multidimensional scale for measuring healthcare service quality (HCSQ), based on modified Brady and Cronin's hierarchical service quality model. The study also investigated HCSQ and its ability to predict important service outcomes through two different models. In the first model, direct effects of service quality dimensions, namely physical environment quality (comprising ambient condition, social factor and tangibles), interaction qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
117
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(137 citation statements)
references
References 22 publications
9
117
0
4
Order By: Relevance
“…In India, several studies have been conducted to propose a service quality measurement model and quality dimensions, such as nursing care, physician care, infrastructure, environment, outcome, medical services, discharge process, administrative/operation and social responsibility (Aagja & Garg, 2010;Chahal & Kumari, 2010;D'Souza & Sequeira, 2012). A Taiwan study used a two-dimension service quality model: competence and interpersonal quality (Chen & Cheng, 2010), whereas for a study in Japan, functional and technical quality were used (Eleuch, 2011).…”
Section: Health Care Service Quality Measurementmentioning
confidence: 99%
“…In India, several studies have been conducted to propose a service quality measurement model and quality dimensions, such as nursing care, physician care, infrastructure, environment, outcome, medical services, discharge process, administrative/operation and social responsibility (Aagja & Garg, 2010;Chahal & Kumari, 2010;D'Souza & Sequeira, 2012). A Taiwan study used a two-dimension service quality model: competence and interpersonal quality (Chen & Cheng, 2010), whereas for a study in Japan, functional and technical quality were used (Eleuch, 2011).…”
Section: Health Care Service Quality Measurementmentioning
confidence: 99%
“…However, because core service tangibles were not well addressed, another group of researchers developed different tools to measure service quality in hospitals (Aagja & Garg, 2010;Andaleeb, 1998;Chahal & Kumari, 2010;Chen & Cheng, 2010;Choi, Cho, Lee, Lee, & Kim, 2004;Dagger, Sweeney, & Johnson, 2007;D'Souza & Sequeira, 2012;Duggirala, Rajendran, & Anantharaman, 2008;Eleuch, 2011;Hasin, Seeluangsawat, & Shareef, 2001).…”
Section: Service Quality Measurementsmentioning
confidence: 99%
“…The model refers to service quality as a comparison differentiation between customer expectation and the actual performance of the service received (Parasuraman, Zeithaml, & Berry, 1985) based on five dimensions, which are tangible, reliability, responsiveness, assurance, and empathy. Chahal and Kumari (2010) suggested that patients judge the quality of the healthcare received on three dimensions, which are the physical environment, interaction quality, and outcome quality. This model has also been tested in measuring the healthcare service quality of hospitals in Asian countries (Butt & de Run, 2010;Sohail, 2003).…”
Section: Healthcare Service Qualitymentioning
confidence: 99%